2021
DOI: 10.1093/g3journal/jkab008
|View full text |Cite
|
Sign up to set email alerts
|

Current genetic conservation of Chinese indigenous horses revealed with Y-chromosomal and mitochondrial DNA polymorphisms

Abstract: To investigate the genetic diversity of Chinese indigenous horses and determine the genetic status of extant horse breeds, novel Y chromosomal microsatellite markers and known Y chromosomal SNPs and mtDNA loop sequences, were employed to study the genetic diversity levels of 13 Chinese indigenous horse populations and four introduced breeds. Sixteen Y-chromosomal microsatellite markers, including seven newly identified loci, were used in the genotyping. The results showed that 4 out of the 16 loci were highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…These haplotype distributions highlight the replacement of autochthonous Y chromosomes with the import of stallions belonging to three paternal lines (ancestral line, Neapolitan/Oriental and Thoroughbred wave) for the improvement of native breeds. Contrary to these findings, Chinese indigenous horse populations seem to have preserved their genetic diversity because they have not been subjected to intensive selection, thus presenting a particular genetic pattern and unique MSY haplotype variants [ 133 , 135 , 138 , 141 , 142 ]. A recent study focused on a large sample of Chinese horses filled the known gap in the worldwide context by adding information on the Asian populations not previously analysed [ 142 ].…”
Section: The Horse Y Chromosome’s Variationmentioning
confidence: 82%
See 2 more Smart Citations
“…These haplotype distributions highlight the replacement of autochthonous Y chromosomes with the import of stallions belonging to three paternal lines (ancestral line, Neapolitan/Oriental and Thoroughbred wave) for the improvement of native breeds. Contrary to these findings, Chinese indigenous horse populations seem to have preserved their genetic diversity because they have not been subjected to intensive selection, thus presenting a particular genetic pattern and unique MSY haplotype variants [ 133 , 135 , 138 , 141 , 142 ]. A recent study focused on a large sample of Chinese horses filled the known gap in the worldwide context by adding information on the Asian populations not previously analysed [ 142 ].…”
Section: The Horse Y Chromosome’s Variationmentioning
confidence: 82%
“…In 2017, Librado and colleagues analysed the genomes of 14 horses lived from Bronze to Iron Ages, confirming the presence of a large genetic diversity in the early stages of domestication [ 117 ]. Recently, the presence of the most ancient paternal lines in Chinese native horses was confirmed through the analysis of 16 Y-chromosomal microsatellite markers, thus reporting for the first time seven novel microsatellite loci [ 135 ], in addition to those previously detected [ 130 , 132 , 136 ]. Among them, four were highly polymorphic only in Chinese local populations and the analysis of the genetic relationships between all the 268 male horses analysed allowed for the identification of 19 Y-chromosomal haplotypes.…”
Section: The Horse Y Chromosome’s Variationmentioning
confidence: 94%
See 1 more Smart Citation
“…In the Ming Dynasty (A.D.1368–1644), a market for exchanging tea for horses was established in Tianzhu County, and horses from Inner-Mongolia and the Qinghai–Tibet Plateau were gathered in the place, which facilitated gene exchange between the introduced horses and the local horses [ 22 ]. Our previous study with Y chromosomal microsatellites also indicated that the Mongolian horse, the Chakouyi horse, and the Tibetan horse have close genetic links [ 3 ]. The Kazak horse is an ancient indigenous breed distributed in Xinjiang Province along the Silk Road.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on Chinese indigenous horses with mtDNA showed that the haplotype diversity of Chakouyi horses was relatively high compared with other Chinese indigenous horse breeds (CHBs), which indicated that there are plentiful maternal lines in Chakouyi horses [ 2 ]. Analysis with Y-chromosomal microsatellite DNA revealed that the Chakouyi horse has a close genetic link with the Mongolian horse [ 3 ]. Another study with whole genome SNP array indicated that the Chakouyi horse is one of the most likely ancestors of the Jinjiang horse, an indigenous horse breed from the southeastern coasts of China [ 4 ].…”
Section: Introductionmentioning
confidence: 99%